Genetic Inhibition of Receptor Interacting Protein Kinase-1 Reduces Cell Death and Improves Functional Outcome After Intracerebral Hemorrhage in Mice. Issue 9 (September 2017) - Lule, Sevda; Wu, Limin; McAllister, Lauren M.; Edmiston, William J.; Chung, Joon Yong; Levy, Emily; Zheng, Yi; Gough, Peter J.; Bertin, John; Degterev, Alexei; Lo, Eng H.; Whalen, Michael J.
Abstract : Background and Purpose—: Recent studies using cultured cells and rodent intracerebral hemorrhage (ICH) models have implicated RIPK1 (receptor interacting protein kinase-1) as a driver of programmed necrosis and secondary injury based on use of chemical inhibitors. However, these inhibitors have off-target effects and cannot be used alone to prove a role for RIPK1. The aim of the current study was to examine the effect of genetic inhibition of the kinase domain of RIPK1 in a mouse ICH model. Methods—: We subjected 2 lines of mice with RIPK1 point mutations of the kinase domain (K45A and D138N), rendering them kinase inactive, to autologous blood ICH and measured acute cell death and functional outcome. Results—: Compared with wild-type controls, RIPK1 K45A/K45A and RIPK1 D138N/D138N had significantly less cells with plasmalemma permeability, less acute neuronal cell death, less weight loss and more rapid weight gain to baseline, and improved performance in a Morris water maze paradigm after autologous blood ICH. In addition, mice systemically administered GSK′963, a potent, specific, brain penetrant small molecule RIPK1 inhibitor, had reduced acute neuronal death at 24 hours after ICH. Conclusions—: The data show that the kinase domain of RIPK1 is a disease driver of ICH, mediating both acute cell death and functional outcome, and support development of RIPK1 inhibitors as therapeutic agents for human ICH. Abstract : Supplemental Digital Content is available in the text.